The defective gut colonization of Candida albicans hog1 MAPK mutants is restored by overexpressing the transcriptional regulator of the white opaque transition WOR1 - Elvira Román; Daniel Prieto; Susana Hidalgo-Vico; Rebeca Alonso-Monge; Jesús Pla (Virulence, 2023)
ABSTRACTThe transcriptional master regulator of the white opaque transition of Candida albicans WOR1 is important for the adaptation to the commensal lifestyle in the mammalian gut, a major source of invasive candidiasis. We have generated cells that overproduce Wor1 in mutants defective in the Hog1 MAP kinase, defective in several stress responses and unable to colonize the mice gut. WOR1 overexpression allows hog1 to be established as a commensal in the murine gut in a commensalism model and even compete with wild-type C. albicans cells for establishment. This increased fitness correlates with an enhanced ability to adhere to biotic surfaces as well as increased proteinase and phospholipase production and a decrease in filamentation in vitro. We also show that hog1 WOR1OE are avirulent in a systemic candidiasis model in mice.